Experience report: nursing consultation in LIBRAS elaborates in a illustrative video SAE/CTA - Mikaelly dos Santos Martins, Thayane; Luanna Chaves Conceição, Thaisy; do Socorro Pereira de Miranda, Karol; Silva de Moraes, Leopoldo; Padilha Barros, Eduardo; Almeida do Espírito Santo, Joyce; Raquel Tapajos Figueira, Luiza; Suely Pinheiro de Almeida, Clea (Seven Editora, 2023)
The care of patients with hearing loss by the health professional requires differentiated instruments that guarantee the quality of the health service. The need for new technologies in the nursing professional sphere is related to the improvement in the quality of services.  Verbal and nonverbal communication is essential for the realization of health care in nursing so that the recipient and the sender can transmit the meaning of the message, regardless of the code and communication channel.  Activity elaborated in the discipline of Nursing Relationship and Communication had as main factor to show students the importance of a qualified nursing professional and that many of the times its differential will be in communication. The methodology used for the performance was a video and script produced by undergraduate nursing students. The theme used was a nursing consultation at Língua Brasileira de Sinais (LIBRAS)   at Sistema Único de saúde (SUS) in  a SAE/CTA SAE/CTA Testing and Counseling Center. DOI: https://doi.org/10.56238/tfisdwv1-050